The rule against hearsay : its exceptions under the Evidence Act 1950 and Islamic legal principle - Afridah binti Abas (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2008)
The rule against hearsay has been traditionally regarded as one of the most fundamental and at the same time most confusing of the law of evidence. Accordingly, there exist uncertainties with regards to the scope of the rule, which resulted to a very relevant and significant evidence may be shut out just because it infringes the hearsay rule. Even though there is no statutory definition of hearsay evidence, the court in Malaysia recognized the rule against hearsay as applicable in Common Law. The thesis analyzes the nature and the scope of the hearsay rule under the Malaysian Law. The main aim of the study is to analyze the admissibility of the hearsay evidence as provided by the Malaysian Evidence Act 1950. The study examines the provisions provided for the exceptions of the hearsay rule in order to look to the sufficiency of such provisions in ensuring the relevant evidence will be admissible. The examination extends to the cases decided by the court in Malaysia. Reference is made to the cases which have been decided in common law as well as other commonwealth countries whenever appropriate. The study includes the examination on the rule against hearsay under Islamic Law. The thesis examines shahddah as one way of proof in Islamic law, the conditions for its admissibility, the admissibility of shahddah 'aid shahddah and shahddah bi al-tasdmu', the conditions for the acceptance and the number of witnesses required to give such evidence. As Malaysia has dual-courts system, the study extends the examination on the admissibility of hearsay evidence under the Syariah Court Evidence Enactments/Act and its application in the Syariah Court. The thesis evidently proves that, the existing provisions in the Malaysian Evidence Act 1950 on the admissibility of hearsay evidence should be broadened. The thesis also reveals that even though the hearsay rule should remains inadmissible, the court should be given a wide power to look to the weight of the hearsay evidence in order to determine whether it is admissible or not.